Quantitative Analysis of Entrepreneurial Orientation and Managerial Competence on Cooperative Performance in Indonesia - Fahmi, Indra; Farida (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
Several cooperatives in Indonesia have struggled to maintain consistent growth and achieve sustainable performance, facing challenges from market competition, limited managerial capacity, and rapidly changing economic conditions. The declining performance of several cooperatives in Indonesia highlights the need to understand strategic factors that influence organizational effectiveness. This study aims to examine the effects of entrepreneurial orientation and managerial competence on cooperative performance and to assess the mediating role of innovation. Using a mixed-method approach, the research synthesises qualitative and quantitative insights from 32 academic and institutional sources and employs regression and mediation analyses to evaluate six hypotheses. The findings show that entrepreneurial orientation significantly enhances both performance and innovation, with innovation partially mediating this relationship. Meanwhile, managerial competence exerts a strong direct influence on performance but does not demonstrate a significant indirect effect through innovation. These results indicate that entrepreneurial orientation contributes more dynamically to cooperative development through innovation pathways, whereas managerial competence strengthens operational stability. The study provides integrated evidence on the strategic and structural dynamics necessary to improve cooperative performance in Indonesia.